Short paper: Secure multi-user transmission using CoMP directional modulation - Marwan, Yusuf; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers, 2015)
Directional Modulation is a recently developed multi-antenna technique for secure transmission. It allows to transmit signals in desired directions while distorting the signal in the other directions. To secure the transmission in a scenario where eavesdropper is in the same direction as legitimate user, a coordinated multipoint scheme is proposed to have a location-specific secure communication that works even when a rich scattering environment is not available. Simulations are presented to verify the proposed scheme using 3 base stations.
Keywords: Antenna Arrays; Radar; Frequency Increment